Co-producing research a community development approach - Banks, Sarah ca. 20./21. Jh; Hart, Angie 1963-; Pahl, Kate 1962-; Ward, Paul (Connected communities (Bristol, England), 2019)
This book shows how community groups can work in partnership with universities to imagine better futures and make them happen, co-producing knowledge to achieve positive change